2018
DOI: 10.18393/ejss.337222
|View full text |Cite
|
Sign up to set email alerts
|

Does hazelnut husk compost (HHC) effect on soil water holding capacity (WHC)? An environmental approach

Abstract: In this study, we applied hazelnut husk waste that was composted by using microbial biotechnological techniques into soil in the field conditions. The hazelnut husk compost (HHC) was applied in two hazelnut orchards having different textures such as sandy loam (SL) and clay loam (CL) soils and used different application rates (0, 1.25, 2.5, 5.0, 7.5 and 10 t da-1). Soil sampling was done four times in a year (spring, summer, fall and winter). We investigated the effects of HHC on soil water holding capacity re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
(16 reference statements)
0
3
0
Order By: Relevance
“…Positive effects on soil properties caused by hazelnut husks were also reported by Ozdemir et al [34] where the authors suggested that hazelnut husks could be used in composted mixes with wastewater biosolids for the production of ornamental plants. Moreover, Aşkın and Aygün [35] highlighted the beneficial impact of hazelnut husk compost on soil organic matter content and water holding capacity, while Gülser et al [36] and Gülser and Candemir [37] indicated the slow mineralization rate of hazelnut husks and the improvements they induce in soil hydraulic properties.…”
Section: Resultsmentioning
confidence: 99%
“…Positive effects on soil properties caused by hazelnut husks were also reported by Ozdemir et al [34] where the authors suggested that hazelnut husks could be used in composted mixes with wastewater biosolids for the production of ornamental plants. Moreover, Aşkın and Aygün [35] highlighted the beneficial impact of hazelnut husk compost on soil organic matter content and water holding capacity, while Gülser et al [36] and Gülser and Candemir [37] indicated the slow mineralization rate of hazelnut husks and the improvements they induce in soil hydraulic properties.…”
Section: Resultsmentioning
confidence: 99%
“…Macadamia husk compost increased the soil potential available water (PAW) in both seasons, while the effect of inorganic fertilizer was non-significant, as expected. The greater PAW with application of MHC was likely due to a similar increase in soil organic matter [43,44] as reflected by the significant positive correlation between SOM and PAW (Table 6). Organic matter affects water holding capacity by improving soil structure, soil aggregate stability, particle size, and total porosity [45].…”
Section: Discussionmentioning
confidence: 93%
“…The VWC necessary to prevent unrecoverable and permanent wilting (the permanent wilting point, PWP) for composts ranges between 20 and 30% (Aşkın & Aygün, 2018).…”
Section: Soil Volumetric Water Content and Temperaturementioning
confidence: 99%